Keeping Up With Rising (Quality) Demands? The Transition of a Wild Food Resource to Mass Market, Using the Example of Baobab in Malawi - Meinhold, Kathrin; Darr, Dietrich (Frontiers in Sustainable Food Systems, 2022)
The importance of wild food resources, particularly from our forests, is increasingly recognized in the context of food systems transformation and derived products are increasingly also entering modern food supply chains. The transformation of a wild, solely traditionally used resource to a product available in retail, however, has consequences, not all of which are currently well understood. Using the rapidly increasing commercialization of baobab fruit products in Malawi as a case study we, therefore, aim to shed light on aspects such a transformation may have on product quality and supply chain organization. Using a mixed-methods approach a total of 68 baobab value chain actors targeting either formal or informal markets were interviewed, focusing on perceived baobab quality characteristics as well as linkages across the value chain, concurrently collecting product samples if the interviewees had these at hand. The baobab supply chain was shown to have elongated in recent years, with a variety of actors now active on the scene, including baobab collectors, a variety of traders often directly picking up baobab resources at source, microenterprises producing baobab ice lollies for informal markets, or more formal juice processors targeting retail outlets. A broad variety of harvest, storage, or processing practices was observed and product quality differed widely, whereas mycotoxins were detected in two of the analyzed samples. Storage of baobab products can last several months with harvesting activities peaking in April, yet sales dominating in the hot months toward the end of the year. Dryness was commonly identified as the most important quality indicator, but other factors such as cracks in the shell were more heavily disputed amongst different value chain actors. Although different quality standards have to be observed to be able to sell in formal retail outlets, risks of low-quality baobab entering formal retail outlets remains with the majority of more formal baobab processors obtaining their raw material via informal pathways. There is a dire need to strengthen the institutional framework and enabling environment to foster the best-possible integration of forest resources into prevailing agri-food systems and enable the production of high-quality products for both the formal and the informal sector.